Atomism and Composition. (13th October 2017) - Uzquiano, Gabriel
Abstract : Atomism is the thesis that every object is composed of atoms. This principle is generally regimented by means of an atomicity axiom according to which every object has atomic parts. But there appears to be a sense that something is amiss with atomistic mereology. We look at three concerns, which, while importantly different, involve infinite descending chains of proper parts and have led some to question standard formalizations of atomism and composition in mereology.